Township incubator programs impact on entrepreneurial behaviour? - Moitse, Daniel Tshepo (Graduate School of Business (GSB), 2022)
Unemployment and poverty especially among the youth have remained major challenges threatening the economic growth and development of townships. “Poverty Trends in South Africa” report, released by (Statistics SA 2017), cites that more than half of South Africans were poor in 2015, with the poverty headcount increasing to 55.5 percent from a low of 53.2 percent in 2011. These challenges therefore demand that the youth be empowered with creative entrepreneurial skills which is one of the skills available to them, in order to make an invaluable contribution to their life and communities. Entrepreneurship is one of the tools to eliminate unemployment and improve economic growth, as result see an increase in entrepreneur incubation center's which are sponsored by government, universities and private companies in townships. These incubations are there to assist entrepreneurs grow their business by providing support and financial assistance. However, despite the rise these incubation programs we don't see their spin-off or benefit in society particularly in townships. They have problems of management, poor infrastructure, poor access to funding for entrepreneurs, lack of entrepreneurial start up programmes, poor or lack of mentoring and coaching problems, and lastly lack to access networks. The main research question is how does enrolling in entrepreneur incubation program impact entrepreneurial behaviour of township entrepreneurs?? A qualitative research approach was chosen as the methodology because this approach underpins an understanding and interpretation of meaning as well as intentions underlying human interaction. Data was collected using semi- structured interviews and 45 semi-structured interviews were conducted. The major findings of the study are as follow:  Incubators in the Northern Cape provides mixture of services in relations to first, second, third and fourth generations incubators. The majority of these incubators are considered weak as they provide only basic services which is shared office facilities to incubatees. The services such mentoring and coaching, training, Wi-Fi, access to finance and networking are lacking. This is considered weakness in terms of theory of incubation.  There is also confusion regarding the typology of incubators. In the Northern Cape we have two mixed incubators, one economic development incubator and one Technology incubator. The incubator missing is the Basic research incubator that should aimed at research and discovery of innovations.  We have also discussed the different success factors of incubation and rated each incubator based on these factors. The majority of incubators performed dismally and are regarded as bad incubators.  The entrepreneurial environment and entrepreneurial resourcefulness will ultimately affect entrepreneurial behaviour. In nutshell, the entrepreneurial environment is government legislation that create conducive environment for incubation but what is lacking is practical support from government. Entrepreneurial resourcefulness which is incubation services offered to entrepreneurs. Incubation centres offered poor services to entrepreneurs. As result the entrepreneurial behaviors of entrepreneurs have not been affected as much or improved during the period of incubation. Lastly, we recommend that there must be a System approach to incubation, incubators adopt incubation model that focus on the needs and circumstance of community. Incubators must have functioning and expert advisory board, business plan and be financially viable in order to survive in the new economy. We also recommend that incubator employ the services of expert professional with experience and qualification in SMME development, business management and understand entrepreneurship or have been entrepreneurs themselves. The purpose of this study was to explore whether these incubators developed the entrepreneurial behaviors of incubatees in the Northern Cape. We have established that that has not happened as result in the future recommend that incubators concentrate on skills development, mentoring and coaching as key aspects of incubation. They must invest on the personal growth and development of their incubatees.